Penggunaan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Belajar Organ Peredaran Darah Manusia Pada Siswa Kelas V Semester 1 SD Negeri 1 Tegalrejo Kecamatan Purwantoro Tahun Pelajaran 2019/2020 - Sirlanie, Angela (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to improve learning outcomes of the Human Circulatory Organs through the use of Problem Based Learning learning models for fifth grade students of SD Negeri 1 Tegalrejo, Purwantoro District, Semester 1 of the 2019/2020 Academic Year. This research is a Classroom Action Research (CAR). The research subjects were students of class V SD Negeri 1 Tegalrejo, totaling 7 students. Data collection techniques using the written test method, observation and documentation. The results showed (1) There was an increase in students' interest in learning compared to the initial condition, namely 43% (less) until the end of the second cycle to 71% (high), (2) There was an increase in student mastery compared to the initial condition, namely 5 students (71 ,42%) at the end of the second cycle to 7 students (100%), so that it has reached the level of completeness as set, which is 100%. There was an increase in the average value when compared to the initial condition of 42.85 at the end of the second cycle to 71.42. There was an increase in student interest and learning achievement in Natural Sciences for fifth grade students at SD Negeri 1 Tegalrejo Purwantoro in the odd semester of the 2019/2020 academic year on the material of Circulatory Organs in Humans. This study concludes that by applying the Problem Based Learning method, it can increase students' interest and achievement in science learning.